Determination of Antiphase Domain Boundary Annihilation Rate in GaAs on Si(001) and the Influence of MOCVD Growth Temperature. (4th May 2016) - Barrett, Caleb Shuan Chia; Martin, Thomas Patrick; Bao, Xin-Yu; Martin, Patrick; Sanchez, Errol; Jones, Kevin Scott
Abstract : The effect of growth temperature on the annihilation of antiphase domain boundaries (APBs) in GaAs grown on 300 mm Si(001) wafers via an industrial III-V metal organic chemical vapor deposition (MOCVD) tool is examined. Samples were grown with identical low temperature nucleation layers to set the APB density before growth of bulk layers at varied temperature. The APB annihilation rate with respect to GaAs film thickness is determined by profiling the APB density in the samples as a function of depth using a combination of chemical etchants. It is found that higher bulk growth temperatures enhance the annihilation of APBs. The increase in APB annihilation rate must be facilitated by a greater portion of APBs kinking from {110} type planes to higher-index planes such as {111} or {112}. The temperature dependence of APB annihilation indicates that there is an associated activation energy for the kinking of APBs.